"The Mediating Role of Employee Innovation between HPWS and Organizational Performance in Indian Manufacturing Sector using a Novel HR Metrics’’ - Sriharsha V J (Journal of Informatics Education and Research, 2025)
Increasing competition and globalization has created tremendous pressure on Indian manufacturing enterprises to improve their productivity and better equip their workforce. High performance work systems (HPWS) have been increasingly adopted in enterprises to gain core competitive advantage and improve organizational performance. Many works have been done on studying the human resource management (HRM) initiatives in creating HPWS and measuring the extent of HPWS. This work analyses the impact of HPWS on the organizational performance of the enterprises with employee innovation as the mediator. The study adopts metric based evaluation and designs scale to measure the HPWS impact on organizational performance. The correlation between the HPWS practices and the metrics of employee innovation and organizational performance are analysed. A system model involving three dimensions of HRM practices, employee innovation, organizational performance is studied in terms of various metrics. The model is validated against data collected from Indian manufacturing enterprises in three categories of small, medium and large.